Nature's Embrace Japan's Aging Urbanites and New Death Rites - Kawano, Satsuki (University of Hawaii Press, 2010)
Based on extensive fieldwork, Nature's Embrace reveals the emerging pluralization of death rites in postindustrial Japan. Low birth rates and high numbers of people remaining permanently single have led to a shortage of ceremonial caregivers (most commonly married sons and their wives) to ensure the transformation of the dead into ancestors resting in peace. Consequently, older adults are increasingly uncertain about who will perform memorial rites for them and maintain their graves. In this study, anthropologist Satsuki Kawano examines Japan's changing death rites from the perspective of those who elect to have their cremated remains scattered and celebrate their return to nature.For those without children, ash scattering is an effective strategy, as it demands neither a grave nor a caretaker. However, the adoption of ash scattering is not limited to the childless. By forgoing graves and lightening the burden on younger generations to care for them, this new mortuary practice has given its proponents an increased sense of control over their posthumous existence. By choosing ash scattering, older adults contest their dependent status in Japanese society, which increasingly views the aged as passive care recipients. As such, this study explores not only new developments in mortuary practices, but also voices for increased self-sufficiency in late adulthood and the elderly's reshaping of ties with younger generations.Nature's Embrace offers insightful discussion on the rise of new death rites and ideologies, older adults' views of their death rites, and Japan's changing society through the eyes of aging urbanites. This book will engage a wide range of readers interested in death and culture, mortuary ritual, and changes in age relations in postindustrial societies